2014
DOI: 10.3844/jcssp.2014.861.868
|View full text |Cite
|
Sign up to set email alerts
|

Qos Based Selection and Composition of Web Services-a Fuzzy Approach

Abstract: Web Services are emerging technologies which satisfy users' requests on the Web. Selecting appropriate services to suit the needs is a huge task. There are a huge number of service providers who offer same type of service, with differences in functional and non functional qualities. A few users may need multiple services at the same moment. So composition of services also becomes important. Moreover the consumers get confused in selecting apt services, which leads to the necessity of an automated service selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The authors in [34] proposed a new fuzzy rule based algorithm for selecting and composing Web services with respect to the users' preference using open source software. In a similar attempt, a formal service composition architecture for service selection is proposed [35], where the authors suggested a trust evaluation method for the service composition plan based on the subjective probability theory.…”
Section: Hybrid Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [34] proposed a new fuzzy rule based algorithm for selecting and composing Web services with respect to the users' preference using open source software. In a similar attempt, a formal service composition architecture for service selection is proposed [35], where the authors suggested a trust evaluation method for the service composition plan based on the subjective probability theory.…”
Section: Hybrid Techniquesmentioning
confidence: 99%
“…This second category includes well-known techniques such as Analytic Hierarchy Process (AHP), eigenvector technique, weighted least square technique, and Delphi technique. The last category is a hybrid combination of objective and subjective techniques [14,17,28,30,32,34,35,38]. Algorithms using the hybrid techniques determine weights directly from the data as well as from the preference information given by domain experts or the users.…”
Section: Introductionmentioning
confidence: 99%